Case Report: Repetitive peripheral magnetic stimulation and task-oriented training improve motor function in chronic severe post-stroke paralysis - Yamamoto, Satoshi; Aoyama, Toshiyuki; Ishii, Daisuke; Ishibashi, Kiyoshige; Kohno, Yutaka (Frontiers in Stroke, 2025)
BackgroundSevere upper-limb motor paralysis following chronic stroke presents a significant rehabilitation challenge, often with limited recovery. This case study explores the effects of repetitive peripheral magnetic stimulation (rPMS) combined with task-oriented training on motor recovery in a patient with chronic stroke and severe upper-limb impairment.MethodsA 50-year-old male with right upper-limb paralysis post-hemorrhagic stroke underwent a 2-week intervention comprising 12 sessions of rPMS targeting the elbow and wrist extensors, combined with task-oriented training. Motor function was assessed using the Fugl-Meyer Assessment (FMA), kinematic analysis, Motor Activity Log (MAL), and electromyographic (EMG) analysis of wrist flexion-extension movements.ResultsThe intervention resulted in a clinically meaningful increase in motor function, reflected in improved FMA scores and greater elbow extension during kinematic analysis. EMG analysis demonstrated reduced co-contractions of wrist flexors and extensors, indicating improved muscle coordination. Despite these gains, recovery of distal voluntary movements, such as wrist dorsiflexion and finger extension, remained limited. As assessed by MAL, upper-limb usage in daily activities showed minor improvements; however, qualitative reports indicated functional gains, including the ability to hold a bottle and assist in closing a car door.ConclusionrPMS combined with task-oriented training shows promise in enhancing motor function in patients with chronic stroke combined with severe upper-limb paralysis, particularly in proximal muscles. Further research involving control groups and objective measures of upper-limb use is necessary to validate these findings and refine intervention protocols.